Evaluasi Faktor Intensitas Tegangan pada Ujung Retak dengan Lubang Penghambar Rambat Petak - Purnowidodo, Anindito (Rekayasa Mesin, 2010)
The evaluation of stress intensity factors in the crack tip interacting with stoping hole of crack growth was conducted by computer simulation, and this was carried out on vareid configuration of stopping hole. The results of the simulation show that the position and zise of stopping hole affect the magnitude of the stress intensity factor. The main cause of the fluctuation of the stress intensity factor is that the stoping hole configuration affects the interaction of stress in the vicinity of crack tip.Keywords : Hole Configuration, Stress Interaction, Stress Intensity Factors